SAT0150 Prospective, intervention, multicenter study of utility of biologic drug monitoring with respect to the efficacy and cost of adalimumab tapering in patients with rheumatic diseases: preliminary results of ingebio study. (15th June 2017) - Ucar, E; Gorostiza, Í; Gόmez, C; Pérez, CE; Dios, JR De; Alvárez, B; Ruibal, A; Stoye, C; Vasques, M; Belzunegui, J; Escobar, A; Trancho, Z; et al.
Abstract : Background: Adalimumab (ADL) tapering based on clinical assessment is a usual practice especially in patients who have achieved clinical remission. Objectives: To analyze how personalized management guided by biological drug monitoring (BDM) in rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS) patients impacts the annual direct costs to the Health System and the quality-adjusted life year with respect to conventional practice in Spain. To evaluate the effectiveness of BDM in the reduction of the number of days with high disease activity compared with conventional practice. Methods: In a pragmatic, non-randomized, non-inferiority clinical study, adult patients treated with ADL (40 mg sc) who remained clinically stable for at least 6 months were recruited in 3 sites. Patients were grouped in Control (CG) and Intervention groups (IG) according to the site. ADL frequency was adjusted based on physician criteria. Patients are assessed at 8 timepoints (8 visits) for up to 18 months. Trough ADL and anti-ADL antibodies levels are measured with Promonitor-ADL and Promonitor-ANTI-ADL (Progenika, SA). BDM data were released only to the IG, and blinded to the CG (managed according to clinical assessment only). Physicians in the IG were not obliged to follow any therapeutic algorithm based on BDM results but could use tests to alter doses based on their judgement. Endpoints include DAS28, BASDAI, BASFI and HAQ-DI scores at every timepoint. Cost-effectiveness will be evaluated according to associated costs and QALY. Results: A total of 169 patients were recruited (disease, N IG, N CG, %) (RA, 30, 33, 37.3%; PsA, 33, 21, 32%; and AS, 46, 6, 30.8%). Median disease duration was 117, 98.5 and 101.5 months for RA, PsA and AS, respectively. At baseline, 10 (16.7%) and 29 (26.6%) patients had low disease activity, 50 (83.3%) and 80 (73.4%) patients were in remission, and median trough ADL levels were 5, 5 and 5, 3 mg/L in the CG and IG, respectively. Mean follow-up (FU) was 505 and 499 days in the CG and IG, respectively. ADL doses were tapered in 22/60 (36, 7%) and 39/109 (35, 8%) patients in the CG and IG, respectively. Patients were in remission an average of 329 vs 344 days in the CG and IG, respectively. The number of flares in the CG and IG was 53 and 69, respectively. The rate of flares per patient-year of FU is 0, 639 vs 0, 463 in the CG and IG, respectively (difference of -0, 176; CI95%: -0, 379 to 0, 0289). The risk of flare is 27, 5% lower in the IG (IRR=0, 7252; CI95%: 0, 4997 to 1, 0578). Quality of life (EQ-5D-5L) was significantly better in the IG at visits 2 (p=0, 001) and 3 (p=0, 035); EQ-5D-5L was higher (although not statistically significant) in the IG in the remaining visits. Average cost of ADL per patient-year was 11.898, 60€ vs 11.240, 81€ (-657.78€) in the CG and IG, respectively. Conclusions: Preliminary results show that rheumatic patients have better quality of life, lower risk of flares and incur in lower treatment costs if patient management is complemented with BDM data. Disclosure of Interest: E. Ucar: None declared, Í. Gorostiza: None declared, C. Gόmez: None declared, C. Pérez: None declared, J. De Dios: None declared, B. Alvárez: None declared, A. Ruibal: None declared, C. Stoye: None declared, M. Vasques: None declared, J. Belzunegui: None declared, A. Escobar: None declared, Z. Trancho: None declared, A. Ruiz del Agua Employee of: Employee of Progenika Grifols, A. Martínez Employee of: Employee of Progenika Grifols, C. Jorquera: None declared, D. Nagore Employee of: Employee of Progenika Grifols